The cove : a novel - Ross, L. J. (Ross, L.J. Summer suspense mysteries., 2026)
"Gabrielle Adams had a good life: a promising publishing career, a devoted fiancé, and a future filled with possibilities. Then everything changed. A serial killer targets commuters on train platforms--striking without warning, disappearing without a trace. Gabrielle is the only one to survive. Struggling to cope with the trauma, she retreats to a quiet coastal village in Cornwall, taking a job running a small bookshop. It's meant to be a fresh start. A second chance. At first, the peaceful town and its rhythms soothe her frayed nerves. But something feels off. Whispers follow her. Footsteps echo at night. And someone knows who she is. As past and present blur, Gabrielle begins to wonder: did she escape the killer... or walk straight into something worse?"-- Provided by publisher.